Adaptation of Phaeobacter inhibens DSM 17395 to growth with complex nutrients. Issue 18 (5th July 2013) - Zech, Hajo; Hensler, Michael; Koßmehl, Sebastian; Drüppel, Katharina; Wöhlbrand, Lars; Trautwein, Kathleen; Hulsch, Reiner; Maschmann, Uwe; Colby, Thomas; Schmidt, Jürgen; Reinhardt, Richard; Schmidt‐Hohagen, Kerstin; et al.
<x xml:space="preserve">Abstract</x> Phaeobacter inhibens DSM 17395, a member of the Roseobacter clade, was studied for its adaptive strategies to complex and excess nutrient supply, here mimicked by cultivation with Marine Broth (MB). During growth in process‐controlled fermenters, P. inhibens DSM 17395 grew faster (3.6‐fold higher μmax) and reached higher optical densities (2.2‐fold) with MB medium, as compared to the reference condition of glucose‐containing mineral medium. Apparently, in the presence of MB medium, metabolism was tuned to maximize growth rate at the expense of efficiency. Comprehensive proteomic analysis of cells harvested at ½ ODmax identified 1783 (2D DIGE, membrane and extracellular protein‐enriched fractions, shotgun) different proteins (50.5% coverage), 315 (based on 2D DIGE) of which displayed differential abundance profiles. Moreover, 145 different metabolites (intra‐ and extracellular combined) were identified, almost all of which (140) showed abundance changes. During growth with MB medium, P. inhibens DSM 17395 specifically formed the various proteins required for utilization of phospholipids and several amino acids, as well as for gluconeogenesis. Metabolic tuning on amino acid utilization is also reflected by massive discharge of urea to dispose the cell of excess ammonia. Apparently, P. inhibens DSM 17395 modulated its metabolism to simultaneously utilize diverse substrates from the complex nutrient supply.